Perancangan Animated Infographics Mengenai Fungsi Niacinamide untuk Kesehatan Kulit untuk generasi Z - Tri Hartini; Bayyinah Nurul Haqq (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Appearance is the first thing people see. With appearance, you can also express yourself. The easiestthing to change your appearance is to maintain healthy skin because healthy skin is the beginning of beauty.Skincare is a way to treat and improve appearance. Adolescence has a very drastic change in appearance.For a good change, the use of skincare containing niacinamide is the right start for teenagers. To providethis information, it can be package in an attractive way as an educational media using Animated infographicsVideo with Pre Production, Production, Post Production methods. Educational media can be obtained fromanywhere. However, for teenagers, Instagram is a social media platform that can be a place to get thiseducational media